The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/jssc.202101013
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of vincristine and tariquidar by liquid chromatography‐tandem mass spectrometry in mouse whole blood using volumetric absorptive microsampling for pharmacokinetic applications

Abstract: A liquid chromatography‐tandem mass spectrometry method was developed and validated for the simultaneous quantification of vincristine and tariquidar in 10 μL of mouse whole blood using volumetric absorptive microsampling devices. Samples were extracted from the devices and quantified against calibrators prepared in a human blood plasma matrix. Separation of vincristine and tariquidar was achieved using a Shimpack XR ODS III C18 stationary phase and H2O and methanol mobile phase solvents containing 0.1% formic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In the work of Rosser et al., the PK assessment of vincristine and tariquidar in mice using an LC‐MS/MS approach was effectively carried out using the VAMS technology. Assessment of both single‐agent therapy and combination therapy over a 24 h period in 10 µL microsamples revealed a 2.3‐fold increase in vincristine drug exposure when combined with tariquidar, which validated the use of the approach for longitudinal analysis of drug exposure in animal studies 27 . Xu et al.…”
Section: Applicationsmentioning
confidence: 75%
See 2 more Smart Citations
“…In the work of Rosser et al., the PK assessment of vincristine and tariquidar in mice using an LC‐MS/MS approach was effectively carried out using the VAMS technology. Assessment of both single‐agent therapy and combination therapy over a 24 h period in 10 µL microsamples revealed a 2.3‐fold increase in vincristine drug exposure when combined with tariquidar, which validated the use of the approach for longitudinal analysis of drug exposure in animal studies 27 . Xu et al.…”
Section: Applicationsmentioning
confidence: 75%
“…90 Guidelines that consolidate the regulatory perspectives on microsampling and support its use in blood sampling have also been added to and reviewed by the which validated the use of the approach for longitudinal analysis of drug exposure in animal studies. 27 Xu et al evaluated the feasibility of CMS coupled to HPLC-MS/MS for mice PK studies using transresveratrol as the model drug. The PK parameters of the drug and its associated metabolites found in the study were comparable with those reported in previous studies, which demonstrated that CMS provides credible samples for subsequent quantitative PK analysis.…”
Section: Volume-limited Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have no pharmacological interactions with chemotherapeutic drugs and have been discovered to be 200 times more powerful than the previous two generations of inhibitors. Zosuquidar (LY335979), mitotane (NSC-38721), laniquidar (R101933) [71], tariquidar (XR9576) [72], ONT-093, elacridar (F12091), annamycin, HM30181, R10933, and biricodar are other examples [73]. According to the 3D QSAR and QSAR activity, the structure of the inhibitors is mostly responsible for producing the inhibitory activities.…”
Section: Substrates Of P-gp and Its Drug Interactionmentioning
confidence: 99%
“…Furthermore, the expression of the T-cell exhaustion markers PD-1 and CTLA-4 was reduced in this subset of CD4+helper-T cells. It has been demonstrated that Th17 and Th1 CD4+T-helper cell subsets secrete anti-tumour inflammatory cytotoxic cy-tokines such as IL-17, IFNg, TNFa, and granzyme [72,104,105]. P-gp-expressing CD4+T cells (CD4+CD73+T cells) were found to secrete more anti-cancer cytokines in tumourinfiltrating breast and ovarian carcinomas.…”
Section: Tumour Immunity and P-gp Functionmentioning
confidence: 99%